ЛАПЛАС ТЕҢЛЕМЕСИ УШЫН ҚОЙЫЛҒАН ШЕГАРАЛЫҚ МӘСЕЛЕНИ ШЕКЛИ АЙЫРМАЛЫ СХЕМА ДҮЗИЎ УСЫЛЫ МЕНЕН ШЕШИУ - Аламинов, М.Х.; Жалелов, Р.М. (FAN va JAMIYAT, 2017)
In the article the decision of a boundary value problem for the equation of Laplas by a construction method of difference schemes is considered. The method of simple iteration for the decision turned out systems of the linear algebraic equations is offered.